Uncovering the Satisfying MOOC Gamification Elements via fuzzy Analytic Hierarchy Process - Hui Ling, Nie; Jen Chen, Chwen; Siong Teh, Chee (International Journal of Engineering and Technology, 2018)
The constantly high drop-out rate in MOOCs remains as a concern of many MOOC providers. Gamification elements in MOOCs are seen to be able to alleviate this problem. As satisfaction is crucial to sustain learnersâ€™ engagement in MOOCs, this study aims to uncover the satisfying gamification elements for MOOC via Fuzzy Analytical Hierarchy Process (FAHP) approach. The study reveals learner-learner interaction as a significant criterion to provide a sense of satisfaction among MOOC learners and the most satisfying gamification elements are leaderboard, badge and opponent and thus, should be considered to be incorporated into MOOCs.Â